Antihumanism in queer theory. (June 2020) - Zanghellini, Aleardo
Although queer theory is distinguished by its antihumanistic rhetoric, in much of queer theory antihumanism is more about performance than substance. This is not a bad thing, for, on those occasions when queer theory takes its antihumanism too seriously, it commits itself to incoherence. I illustrate this through an intertextual critique of Edelman's and Bersani's works. Edelman's celebration of the death drive is internally torn between an amoral standpoint and immoral urges. Unlike recent critical interventions, however, my point is less to impugn queer theory's preoccupation with antinormativity, than the performance of antinormativity that manifests as queer antihumanism.